Gene therapy and imaging in preclinical and clinical oncology: recent developments in therapy and theranostics. (December 2014) - Gehrig, Sebastian; Sami, Haider; Ogris, Manfred
In the case of disseminated cancer, current treatment options reach their limit. Gene theranostics emerge as an innovative route in the treatment and diagnosis of cancer and might pave the way towards development of an efficacious treatment of currently incurable cancer. Various gene vectors have been developed to realize tumor-specific nucleic acid delivery and are considered crucial for the successful application of cancer gene therapy. By adding reporter genes and imaging agents, these systems gain an additional diagnostic function, thereby advancing the theranostic paradigm into cancer gene therapy. Numerous preclinical studies have demonstrated the feasibility of combined tumor gene therapy and diagnostic imaging, and clinical trials in human and veterinary oncology have been executed with partly encouraging results.